Experiments on causal exclusion. (16th March 2021) - Blanchard, Thomas; Murray, Dylan; Lombrozo, Tania
Abstract : Intuitions play an important role in the debate on the causal status of high‐level properties. For instance, Kim has claimed that his "exclusion argument" relies on "a perfectly intuitive … understanding of the causal relation." We report the results of three experiments examining whether laypeople really have the relevant intuitions. We find little support for Kim's view and the principles on which it relies. Instead, we find that laypeople are willing to count both a multiply realized property and its realizers as causes, and regard the systematic overdetermination implied by this view as unproblematic.